Mathematical model for unemployment in Malaysia using dynamic differential equation / Nur Azmina Amirudin - Amirudin, Nur Azmina (2021)
In this study, a mathematical model is developed using a dynamic differential equation by considering three variables which are the number of individuals who are unemployed, the number of individuals working and the number of new vacancies created by the government and private sectors. The paper analysed and evaluated the model of unemployment, the equilibrium point, stability of the equilibrium point and the characteristics of different variables on unemployment. The main objective of this study is to develop a Mathematical model for unemployment in Malaysia. This study also aims to pre-process the unemployment data set and to analyse the characteristics of unemployment using dynamic differential equation. The numerical simulation used was MAPLE. The first step was to find the equilibrium point. Then, the stability of the equilibrium was checked using the variational matrix. Next, the characteristics of unemployed persons were identified with respect to the rate of movement of employed people, the rate of newly created vacancies by the government and private sector, and the rate of unemployed person who starts their own independent work and become self-employment, . The result shows that the value of . It means that if the number of newly created vacancies by the government and private sectors increases, then the rate of unemployment can be reduced. It is also shown that the equilibrium values of unemployed persons and the rate of self-employed are related. It also shows that the value of which means if the rate of self-employed increases, then the rate of unemployment can be reduced. , 2 x  5 x 0 *   ddU 0 5*  dx dU